The Hexaemeral Tradition in Old English Peotry - Smith , Edith Katherine (My University, 1975)
In our search for an understanding of Old English cosmological conceptions we discover that the creation myth is central to the mysteries of the Christian faith, and that the Greek and Latin authors' interpretations of creation, known as "Hexaemera", provide much that is vital and influential to Old English poetic cosmology. My purpose in this dissertation is two-fold. The first is to provide for the Old English biblically-based poems an informing context of Greek and Latin hexaemeral writings drawn mainly from the Fathers of the Church. The second is to examine three Old English texts on creation and paradise as set against the background of the Mediterranean hexaemeral tradition. That a definite and complex accumulation of hexaemeral writings existed from the early patristic era through the Old English period (ca. A.D. 100-750) is confirmed by the wide variety of treatises, tractates, sermons, poems and hymns, assertive and didactic literary genres all revealing one major purpose -- the demonstration of intelligible order in the universe which is to be perceived through a vision of God's wisdom in creation.
From this immense body of traditions about creation and paradise emerges a pattern which suggests to us the hypothesis that the Old English Christian poets, whose access to a broad range of such writings has been established, pondered and incorporated the hexaemeral features and conventions while adding their own variations to the creation theme. An important corollary to this hypothesis is that the Old English accounts of creation and paradise were influenced by an elaborate, lettered, and learned tradition which deserves special critical emphasis. Recent scholars have stressed the need for a comprehensive study of the potentialities of allusion in Old English poems to traditional Christian allegorical and tropological interpretations, as well as a study of the scholarly habits of perception which distinguished the monastic and ecclesiastical writings of the Middle Ages. This thesis is intended to fill a small aspect of this need in its exploration of the lettered traditions of creation which preceded and existed alongside Anglo-Saxon civilization.
In order to develop this thesis I have categorized its two parts, respectively, as the patristic and poetic traditions. Part One offers an inquiry into the exegetical treatment of creation and paradise revealed in the Fathers, the Christian Latin poets, and related sources. The exploration is not intended to be comprehensive but representative in a critical mode directed towards illuminating our understanding of certain seminal concepts from which radiated further interpretations of creation in the Old English poetic canon. The figural levels of meaning perceived by patristic authors in such archetypal symbols as the primordial ocean, the green plain and golden groves of Eden, the luminaries of day and night, the fire and hail, snow and vapour of creation, contribute to our understanding of the Old English moulding of creation myths.
In Part Two, the critical scope of the study focusses in three separate chapters on the creation :features of the Junius Genesis A and Christ and Satan, and the paradisal elements in the Exeter Phoenix. Equipped with a knowledge of the main features of the Mediterranean hexaemeral tradition, we are enabled to perceive the divergent treatment of creation themes in the relevant Old English texts. The intricacies of Christian exegesis can amplify our appreciation of the more concise Old English poetic hexaemeral in which the major emphasis is on tradition drawn from late classical antiquity, pagan Germanic concepts, and· biblical and patristic imagery. This assertion is not to imply that the Old English poetic texts merely present successive interpretations of creation and paradise without adding any new dimension. The hexaemeral tradition in the imaginations of the Old English poets loses the rigid character of dogma and develops into a vision of the world as cosmopoesy.
The boundaries of investigation in this thesis are necessarily limited. I have selected a scope of study within the main documentable collection of traditions which aided in shaping Old English cosmogonic mythology. Throughout the study I argue for the significance of, and the indispensable need for, knowledge of Christian traditions in the area of Old English hexaemeral writings which constitute mythopoeic or imaginative literature in contrast to the homiletic character of influential patristic doctrine.
Keywords: Old English; cosmological conceptions; Christian faith; Hexaemera; poetic cosmology